COMMUNITY DIGITAL ENTREPRENEURSHIP TRAINING AS A SOLUTION TO ECONOMIC RECOVERY IN ACEH - Hasbi; Saiful Bahgia; Ajrul Amilin; Armanda Butar Butar (Lembaga Riset dan Inovasi Kreyat Center, 2023)
The COVID-19 pandemic has paralyzed the Indonesian economy both regionally and nationally and even at the international level. The impact of this pandemic is a big problem for the nation today, and the big problems facing the Indonesian people right now are unemployment and poverty. The poverty rate in Indonesia has jumped drastically since Indonesia was hit by the Covid-19 pandemic in 2020, many productive people in Indonesia have lost jobs, so many unemployed people have created new problems, namely poverty and unemployment. Community Digital Entrepreneurship Assistance aims to increase community productivity and welfare and increase Literacy, insight, and understanding of digital-based Entrepreneurship; There is good and measurable planning for the community in starting an entrepreneurial plan; Creation of new jobs for people of productive age; Suppressing the growth rate of poverty and unemployment in Aceh. The method of implementing the activity is in the form of technical guidance and the formation of community digital groups/communities which produce the outputs of this activity are a formation of a digital entrepreneur community (Digital Entrepreneur Community) and team consolidation and digital-based entrepreneurship technical guidance.